ANALISIS JABATAN, PERENCANAAN SUMBER DAYA MANUSIA DAN REKRUTMEN TERHADAP KINERJA PEGAWAI - Hildani, Hildani; Kamaruddin (LPPM-UNIKI, 2024)
This research aims to empirically analyze job analysis, human resource planning and employee recruitment on employee performance. In the form of a case study at the Bireuen Regency Education and Culture Office. Using quantitative research with path analysis. Data collection was carried out using a questionnaire on a sample of 65 employees. The research results show: (1) There is a causal relationship between exogenous variables, namely job analysis, HR planning and recruitment with an average correlation value of 0.53. (2) There is a direct and indirect influence of job analysis on employee performance of 35.29%. (3) There is a direct and indirect influence of HR planning on employee performance of 43.97%. (4) There is a direct and indirect influence of recruitment on employee performance of 40.67%. (5) Simultaneously the contribution of job analysis, HR planning and recruitment had an impact on the performance of Bireuen Regency Education and Culture Service employees by 79.1%.